THE INFLUENCE OF APPLICATION SYSTEM QUALITY CONTROL IN THE PERFORMANCE OF AUDITORS (EMPIRICAL STUDIES) ABC KAP IN SOUTH JAKARTA IN 2009 – 2013 - Blasius Febriyanto; Trisno Saputro; Dwi Asih Surjandari (STIE Binaniaga, 2016)
This study has the objective to determine the effect the independence, professionalism, professional ethics and integrity of client understanding of the performance of the auditors on an empirical study of the public accounting firm ABC in South Jakarta. The method used in sampling is convenience sampling. The number of questionnaires distributed 150 questionnaires. However, the back and can be used for further analysis of 120 questionnaires. Analysis of the data is to use multiple linear regression coefficient of determination see, the value of F statistics and statistical t. Results of this study showed that the independence, professionalism and ethics of the profession positive effect on the performance of auditors while understanding client integrity negative effect on the performance of auditors.Keywords: Independent, Profesionalisme, Ethic of Professional, Client Integrity and Auditors Performance